PENGARUH LAMA WAKTU PENGADUKAN BETON NORMAL DAN PENAMBAHAN FOSROC TERHADAP KUAT TEKAN BETON - A, Arman.; Agus, Agus; Nofrizal, Nofrizal; Medriosa, Hamdeni; Rafli, Muhammad (Ensiklopedia of Journal, 2024)
This study aims to determine the effect of normal concrete mixing time and the addition of fosroc addictive substance on the compressive strength of concrete. The stirring time was varied for 3 different times, namely 3, 8, and 20 minutes, where from each time variation the compressive strength of the concrete was tested. This research was conducted by comparing the stirring time of 3, 8, and 20 minutes. The results of testing the compressive strength of concrete aged 28 days for concrete with normal concrete stirring time of 3 minutes 27.55 MPa, 8 minutes 30.38 MPa, 20 minutes 29.40 MPa, and concrete with additional Fosroc 3 minutes 30.19 MPa, 8 minutes 29.44 MPa, 20 minutes 20.57 MPa. And on the results of the slump test for concrete with a normal mixing time of 3 minutes 4.5 cm, 8 minutes 7.5 cm, 20 minutes 4 cm, and concrete with additional Fosroc 3 minutes 4 cm, 8 minutes 5 cm, 20 minutes 3, 5 cm. From these results, the standard planned for k250 concrete is 26 MPa, in this study the average compressive strength achieved the planned results, except for a time variation of 20 minutes with the addition of fosroc which was below the planned one, which was 20.57 MpaKeywords: Stirring time, compressive strength